Advances in visual methodology - Pink, Sarah (Los Angeles : Sage Publications, 2012)
"Sarah Pink draws together in a single volume a set of key writings on advances and explorations that sit at the innovative edge of theory and practice in contemporary visual research. Advances in Visual Methodology presents a critical engagement with interdisciplinary practice in the field of visual research and representation, examining the development of visual methodology as a field of interdisciplinary and post-disciplinary practice that spans scholarly and applied concerns. The book explores how new practice-based, theoretical and methodological engagements are developing and emerging in research practice; the impact new approaches are having on the types of knowledge visual research produces and critiques; the ways visual research intersect with new media; and the implications of this for social and cultural research, scholarship and intervention."--Publisher's website.
Part 1: Key developments and issues. Advances in Visual Methodology: An Introduction / Sarah Pink ; Visual Ethics in a Contemporary Landscape / Andrew Clark. -- Part 2: Visual practices and visualing practice. The Politics and Practices of Looking: CCTV Video and Domestic Kitchen Practices / Lydia Martens ; Video in Analytic Practice / Jon Hindmarsh and Dylan Tutt ; Virtual/Visual Ethnography: Methodological Crossroads at the Intersection of Visual and Internet Research / Elisenda Ardévol. -- Part 3: New visuals spatialities. Community Mapping as Auto-Ethno-Cartography / Cristina Grasseni ; Visual Ethnography and the Internet: Visuality, Virtuality and the Spatial Turn / Sarah Pink ; Geomedia-Based Methods and Visual Research. Exploring the Theoretical Tenets of the Localization and Visualization of Mediated Social Relations with Direct Visualization Techniques / Francesco Lapenta. -- Part 4: Public scholarship, arts and visual intervention. Ethno-Mimesis and Participatory Arts / Maggie O'Neill ; Healing Mirrors: Body Arts and Ethnographic Methodologies / Christina Lammer ; Digital Technologies, Visual Research and the Non-Fiction Image / Roderick Coover with Pat Badani, Flavia Caviezel, Mark Marino, Nitin Sawhney, William Uricchio. -- Part 5: Towards an interdisciplinary visual methodology? An Anthropologist in the Film Archives: Interdisciplinary Approaches / Marcus Banks ; Visualizing Interior Worlds: Interdisciplinary Routes to Knowing / Susan Hogan and Sarah Pink ; Contemplating the State of Visual Research: An Assessment of Obstacles and Opportunities / Luc Pauwels.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Visual sociology -- Research -- Methodology; Social sciences -- Research -- Audio-visual aids; Electronic books